Activating PI3Kδ mutations in a cohort of 669 patients with primary immunodeficiency. (9th November 2015) - Elgizouli, M.; Lowe, D. M.; Speckmann, C.; Schubert, D.; Hülsdünker, J.; Eskandarian, Z.; Dudek, A.; Schmitt‐Graeff, A.; Wanders, J.; Jørgensen, S. F.; Fevang, B.; Salzer, U.; et al.
Summary: The gene PIK3CD codes for the catalytic subunit of phosphoinositide 3‐kinaseδ (PI3Kδ ), and is expressed solely in leucocytes. Activating mutations of PIK3CD have been described to cause an autosomal dominant immunodeficiency that shares clinical features with common variable immunodeficiency (CVID). We screened a cohort of 669 molecularly undefined primary immunodeficiency patients for five reported mutations (four gain‐of‐function mutations in PIK3CD and a loss of function mutation in PIK3R1 ) using pyrosequencing. PIK3CD mutations were identified in three siblings diagnosed with CVID and two sporadic cases with a combined immunodeficiency (CID). The PIK3R1 mutation was not identified in the cohort. Our patients with activated PI3Kδ syndrome (APDS) showed a range of clinical and immunological findings, even within a single family, but shared a reduction in naive T cells. PIK3CD gain of function mutations are more likely to occur in patients with defective B and T cell responses and should be screened for in CVID and CID, but are less likely in patients with a pure B cell/hypogammaglobulinaemia phenotype.